Productivity Growth in Agriculture: An International Perspective 2012
DOI: 10.1079/9781845939212.0273
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural productivity and policy changes in sub-Saharan Africa.

Abstract: This chapter uses a non-parametric Malmquist index to measure agricultural TFP growth in sub-Saharan Africa (SSA). The estimates show a flat or declining productivity from the 1960s to the early 1980s followed by moderate TFP growth since then. This recovery in agricultural productivity growth is attributed to the structural adjustment reforms that were implemented in a number of SSA countries beginning around this time and continuing into the 1990s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…Along the same lines, Nin-Pratt (2009) estimates that addressing agricultural productivity factors, such as access to higher yielding seeds, fertilisers, equipment and knowledge would allow West African countries to increase agricultural productivity for rice by a factor of 2, for cotton by 2.6, for maize and coarse grain by 3, and for other crops by as much as 10 to 50%.…”
Section: Iia Productive Capacity Constraintsmentioning
confidence: 96%
See 2 more Smart Citations
“…Along the same lines, Nin-Pratt (2009) estimates that addressing agricultural productivity factors, such as access to higher yielding seeds, fertilisers, equipment and knowledge would allow West African countries to increase agricultural productivity for rice by a factor of 2, for cotton by 2.6, for maize and coarse grain by 3, and for other crops by as much as 10 to 50%.…”
Section: Iia Productive Capacity Constraintsmentioning
confidence: 96%
“…Agricultural growth affects poverty and overall economic growth directly and indirectly through linkages with the non-agricultural sector; at the same time, reinforcing economic activity in rural areas has a significant impact on the disproportionately large number of poor living in those areas (see empirical studies on Ethiopia by Diao and Nin-Pratt, 2007; on Ghana by Breisinger et al, 2008; and findings by Datt and Ravallion, 1998;Christiansen, Demery, and Küh, 2006, who find that agricultural growth had an impact 13.8 times larger than non-agricultural growth on poverty). Nin- Pratt et al (2009) consider poor growth in agriculture to be a key factor behind the overall weak performance of West African economies. The authors stress the mismatch between the old-fashioned, low productivity and high risk production patterns that are still prevalent in the region and the role of the agricultural sector as the main provider of employment, rural livelihoods, export revenues, and more generally national income.…”
Section: The Link To Poverty Reduction and Food Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…Incremental innovative activities not captured in formal R&D can be accounted for by decomposing total factor productivity (TFP) growth into two components viz-aviz technical change and efficiency change. Improvement in the technical change component is considered to be evidence of innovation, while improvement in efficiency-change component is considered to be an evidence of diffusion of new technology [8]. TFP growth estimates and its components allow a much nuanced analysis of the impact of innovation on productivity growth.…”
Section: Introductionmentioning
confidence: 99%
“…The technical aspects of tissue culture and banana-ripening boxes played a part; just as important, however, were the provision of market information and channels to producers [3]. Previous studies have identified a key role of national research and development (R&D) capacities in raising agricultural productivity in developing countries [4], [5], although agricultural R&D capacity in Africa has remained low by international norms [6][7][8]. Nevertheless, countries whose R&D data are patchy or low, may modestly be improving their production practices over time, not through R&D, but rather by innovative and adoptive activities that determine productivity growth.…”
Section: Introductionmentioning
confidence: 99%